Primerjava padavin na ploskvah intenzivnega monitoringa gozdov v Sloveniji - Vilhar, Urša (Gozdarski vestnik, 2017)
Temporal and spatial distribution of precipitation is of great importance for forest ecosystems, as it affects their water supply. At the same time, forests are regulating water flows and affecting the water resources availability in catchments by intercepting precipitation and soil water retention. More detailed information about precipitation distribution in forest ecosystems is necesarry due to climate change, which contributes to changes in precipitation regime and frequency and intensity of extreme precipitation events. The aim of this study was to analyze the precipitation at eight forest monitoring plots in Slovenia from 2004 to 2013, where regular bi-weekly measurements of precipitation in the open, throughfall, stemflow and net precipitation was preformed. Specifically, we were interested in finding out to what extend the net precipitation in forests is affected by geographical location, altitude and tree species mixture. In addition, open field precipitation was compared to the nearest station of the Slovenian Environmental Agency (ARSO). The precipitation amounts differed among the plots due to compex terrain and general spatial precipitation distribution in Slovenia. Mean annual precipitation on plots ranged from 77 % to 103 % of pricipation in the open. Mean annual stemflow on plots with prevailing beech ranged from 2 % to 15 % of precipitation in the open. Mean annual net precipitation on plots were 94 % of precipitation in the open and were increasing with the altitude. The agreement between open field precipitation and the precipitation on ARSO stations was generally good, except for the Fondek in Trnovski gozd and Tratice on Pohorje Mountains plots, which are located in mountainous regions with compex terrain. In case of 60 GozdnVestn 75 (2017) 2 1 UVOD 1 INTRODUCTION Na prostorsko in časovno porazdelitev padavin vplivajo različni dejavniki, kot so geografska lega, bližina morja, topografija, raba tal, urbanizacija in drugo (Diodato, 2005; Šraj in sod., 2008b). V Sloveniji je porazdelitev padavin zelo raznolika, kar je posledica geografske lege Slovenije, razgibanosti njenega površja in značilnosti posameznih vremenskih tipov (Cegnar, 2003; Luis in sod., 2012; Dolinar, 2016). Poleg nadmorske višine ter razporeditve gorskih grebenov in dolin vpliva na prostorsko porazdelitev padavin tudi dejstvo, da večino padavin k nam prinesejo jugozahodni vetrovi (Cegnar, 2003; Sušelj in Bergant, 2006). Porazdelitev padavin v gozdu je odvisna od vrste in intenzivnosti padavin, pa tudi od zgradbe gozda, mešanosti drevesnih vrst, oblike dreves in njihove prostorske razporeditve (Kimmins, 1997), skladiščne zmogljivosti krošenj, hrapavosti debla (Rejic in Smolej, 1988; Zabret, 2013). Pomembni dejavniki so tudi smer in hitrost vetra (Krečmer, 1967) ter izpostavljenost gozdnemu robu (Klaasen in sod., 1996). Količina, oblika in časovna porazdelitev padavin so izredno pomembne za gozdne ekosisteme, saj pomembno vplivajo na njihovo preskrbo z vodo (Vilhar in Simončič, 2012; Vilhar, 2016a). Prepuščene padavine, ki pridejo do gozdnih tal (Waldner in sod., 2014), so skupaj z odtokom po deblu pomemben vir hranil za rastline (Levia in Germer, 2015) ter so pomembne za kemične in biološke procese v tleh (Thimonier, 1998). Hkrati so gozdovi pomembni z vidika prestrezanja padavin (Siegert in sod., 2016) unavailabe precipitation data in regions with complex topography, caution is needed when applying data from the nearest ARSO stations. Direct link between net precipitation and tree species mixtrue was not confirmed due to small number of forest monitoring plots. Furthermore, the plots are geographically so remote that the net precipitation is largely affected by general spatial distribution of precipitation in Slovenia. In order to assess the influence of tree species mixture on net precipitation in forests, study in smaller areas with homogene topography and orography should be preformed including a larger number of forest monitoring plots with diverse shares of tree species.
Keywords: prepuščene padavine; throughfall; odtok po deblu; stemflow; sestojne padavine; net precipitation; mešanost drevesnih vrst; tree species mixture; topografija; topography